2019
DOI: 10.4314/mmj.v31i1.12
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain during pregnancy: Prevalence, risk factors and association with daily activities among pregnant women in urban Blantyre, Malawi

Abstract: Introduction Low back pain (LBP) is a significant musculoskeletal problem during pregnancy with potential to negatively affect the woman's quality of life. Data on LBP among pregnant women in Malawi is almost non-existent. We investigated the prevalence and risk factors of LBP and its association with functional activities in pregnant women in Malawi. Methods We conducted a cross-sectional study in Blantyre, Malawi, from December 2017 to January 2018. Participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
2
33

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(113 citation statements)
references
References 16 publications
7
71
2
33
Order By: Relevance
“…The prevalence estimate of 34% of women reporting PGP and/or LBP was lower than most other comparable studies (40,50,73,206,207,217). Table 6 provides an overview of previous studies, showing a wide range of prevalence estimates, with studies reporting 31% to 90% for LBP, 2% to 74% for PGP and 25% to 86% for PGP and/or LBP (29, 30, 42, 50-52, 69, 198, 206, 217, 232, 233).…”
Section: Prevalence and Severity Of Pelvic Girdle Pain And/or Low Baccontrasting
confidence: 67%
See 2 more Smart Citations
“…The prevalence estimate of 34% of women reporting PGP and/or LBP was lower than most other comparable studies (40,50,73,206,207,217). Table 6 provides an overview of previous studies, showing a wide range of prevalence estimates, with studies reporting 31% to 90% for LBP, 2% to 74% for PGP and 25% to 86% for PGP and/or LBP (29, 30, 42, 50-52, 69, 198, 206, 217, 232, 233).…”
Section: Prevalence and Severity Of Pelvic Girdle Pain And/or Low Baccontrasting
confidence: 67%
“…The Nepali ODI has shown acceptable reliability in Nepalese people with LBP (177) and has been used in a previous study in Nepal (205). Moreover, the ODI has been widely used in pregnancy-related PGP and LBP studies (34,35,50,(206)(207)(208) and has shown good internal consistency, testretest reliability and construct validity for pregnant women with PGP (174). Since we probably have included women with both PGP and LBP, the use of both questionnaires enabled us to cover disabilities from both conditions.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Khanna et al [20] added that LBP occurs due to the size of the abdomen that has increased. Lower back pain increases with increasing gestational age [21], while changes in the uterus causes the center of gravity of change [22]. The improper posture of the mother can cause additional fatigue and stretch in the body of pregnant women, especially in the area of the spine so that it can cause lower back pain [23].…”
Section: B Anxiety Low Back Pain (Lbp) and Sleepmentioning
confidence: 99%
“…Under the influence of plasma, the resulting catalysts can be very different from those prepared by conventional thermal means. This is the major reason that plasmas have been extensively applied for catalyst preparation (Raoof et al, 2013;Wang et al, 2018). In this experiment, the precursors with metallic complex will be vaporized in a hightemperature environment.…”
Section: Discussionmentioning
confidence: 99%